The Influence of Online Customer Reviews and Perceived Quality on Purchase Intention Through Customer Trust of Luxrime Official Shop Cosmetic Products on Shopee - Dina Savira; Jushermi Jushermi; Sriwahyuni Wildah (Westscience Press, 2024)
This research aims to determine the influence of Online Customer Reviews and Perceived Quality on Purchase Intention through Customer Trust of Luxrime Official Shop Cosmetic Products on Shopee . The population in this study were people in Pekanbaru City who knew Luxcrime cosmetic products on the Official Shop Shopee. The sampling technique used in this research is the Non-Probability Sampling technique with the number of samples used being 100 respondents. The data analysis method in this research uses the Structural Equation Modeling - Partial Least Square (SEM-PLS) analysis method with SmartPLS version 4.0 software . The research results show that Online Customer Reviews have a significant effect on Customer Trust, Perceived Quality has a significant effect on Customer Trust, Online Customer Reviews have a significant effect on Purchase Intention, Perceived Quality has a significant effect on Purchase Intention, Customer Trust has a significant effect on Purchase Intention, Online Customer Reviews have a significant effect on Purchase Intention through Customer Trust and Perceived Quality has a significant effect on Purchase Intention through Customer Trust.